Design-management interactions of Malaysia's Kerian Irrigation Scheme - Valera, A.; Desa, M.N.B.M. (International Irrigation Management Institute, 1991)
This study of the Kerian irrigation scheme determines effects of the rehabilitation design and actual management interactions on performance and suggests ways to improve the existing level of system performance. The study also probes , among other things, such shortfalls as overly optimistic management assumptions and the declining interest of farmers in irrigated farming.